STUDY OF POTENTIAL SOURCES OF RAW WATER FOR PDAM KAPUAS REGENCY - Priyoga A. Cahyono; Novitasari Novitasari; Nurfansyah Nurfansyah (INFO-TEKNIK, 2023)
Clean water is one of the most essential needs for humans because all human activities in various aspects of life require clean water. Kapuas Regency has 17 sub-districts and has a population of around 410,446 people based on BPS data in 2020. The purpose of this paper is to determine the amount of clean water needed in Kapuas Regency to serve the needs of the community in the future. The need for clean water for the residents of Kapuas Regency is supplied by PDAM Kapuas, with two intakes located in Selat Sub-District and Mostkau Village. However, the two intakes cannot meet the clean water needs of the population of Kapuas Regency, which is increasing every year. So it is planned to build a new intake so that the clean water needs of the residents of Kapuas Regency can be met. The analytical method used to calculate population projections is the Geometric Method. The geometric method is used to obtain information on long-term development planning obtained from BPS (Central Bureau of Statistics) Kapuas Regency. The results of the geometric method will be known to predict the population in the next few years so that it can also be seen the amount of clean water needed to determine additional raw water sources in Kapuas Regency. The water demand analysis research that has been carried out shows that Kapuas Regency, which has a population of 410,446 people who have a total non-domestic water need in 2020 is1.006.113 liters/day, and the total amount of household and urban water needs is 63,538,127 liters/day. The laboratory tests and direct observations in the field showed that the construction of the new intake selected was in the village of Palangkai. Palangkai Village has a more strategic location because it is included in the freshwater category, namely bypH 6-9 (PP No. 82 of 2001) with a result pH calculation is 6.1, which is closer to the standard than Sei Asam village, which has a pH of 5.1.